The Effect of Phosphorous Fertilization on Indian Pennyworth (Centella asiatica L. Urban) in High Altitude - Sandra Arifin Aziz; Munif Ghulamahdi; Andria Afrida (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2011)
The experiment was conducted to determine the effect of phosphorous fertilization on growth and production of Indian pennyworth (Centella asiatica L. Urban) in the high altitude (1,500 m above sea level/asl). This experiment was carried out at Gunung Putri experimental station Balittro,Cipanas, Cianjur in October 2008 until April 2009. The treatment was laid-out in a Complete Randomized Block Design and consisted of single factor with 5 replications. The factor was P2O5 fertilization i.e. 0, 30, 60, 90, and 120 kg P2O5.ha-1. The results of the experiment showed that P2O5 fertilizer significantly increased the total leaf number, leaf length, the total flower number, leaf thickness of mother plant and production components at 6 month after planting. The highest production (1.34 ton dry weight.ha-1) was achieved by 60 kg P2O5.ha-1. The optimum dosage to improve dry weight production of Indian pennyworth in high altitude was 65.84 kg P2O5.ha-1.Key words: Centella asiatica L., phosphorous fertilization, production